In Vitro Nephrotoxicity Induced by Propanil - Rankin, Gary O. (Environ Toxicol, 2008)
Propanil is a postemergence herbicide used primarily in rice and wheat production in the United States. The reported toxicities for propanil exposure include methemoglobinemia, immunotoxicity, and nephrotoxicity. A major metabolite of propanil, 3,4-dichloroaniline (3,4-DCA), has been shown to be a nephrotoxicant in vivo and in vitro, but the nephrotoxic potential of propanil has not been examined in detail. The purpose of this study was to determine the nephrotoxic potential of propanil using an in vitro kidney model, determine whether in vitro propanil nephrotoxicity is due to metabolites arising from propanil hydrolysis, and examine mechanistic aspects of propanil nephrotoxicity in vitro. Propanil, 3,4-DCA, propionic acid (0.1–5.0 mM), or vehicle was incubated for 15–120 min with isolated renal cortical cells (IRCC; ~4 million cells/mL) obtained from untreated male Fischer 344 rats. Cytotoxicity was determined by measuring lactate dehydrogenase release from IRCC. In 120-min incubations, propanil induced cytotoxicity at concentrations >0.5 mM. At 1.0 mM, propanil induced cytotoxicity following 60- or 120-min exposure. Cytotoxicity was observed with 3,4-DCA (2.0 mM) at 60 and 120 min, while propionic acid (5.0 mM) induced cytotoxicity at 60 min. In IRCC pretreated with an antioxidant, cytochrome P450(CYP) inhibitor, flavin adenine dinucleotide monooxygenase activity modulator, or cyclooxygenase inhibitor before propanil exposure (1.0 mM; 120 min), only piperonyl butoxide (0.1 mM), a CYP inhibitor, pretreatment decreased propanil cytotoxicity. These results demonstrate that propanil is an in vitro nephrotoxicant in IRCC. Propanil nephrotoxicity is not primarily due to metabolites resulting from hydrolysis of propanil, but a metabolite resulting from propanil oxidation may contribute to propanil cytotoxicity.